FINANCIAL RATIO ANALYSIS TO ASSESS PERFORMANCE FINANCIAL PERFORMANCE OF LOCAL GOVERNMENT (Case Study on Surakarta City Government for the 2020-2022 Period) - Vicki Novitasari; Rukmini Rukmini; Desy Nur Pratiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study is t find out and analyze the regional financial Performance of the Surakarta city government in 2020-2022 in terms of the PAD Independence ratio, to find out and analyze the regional financial performance of the Surakarta city government in 2020-2022in terms of the effectiveness ratio, to find out and analyze financial performance. Surakarta city government area in 2020-2022 in terms of efficiency ratios, to find out and analyze the regional financial performance of the Surakarta city government in 2020-2022 in terms of growth ratios. Research is descriptive research. The sample in this in study is the Surakarta City APBD 3 years, namely the period 2020-2022. The data collection method id with documentation. Data analysis techniques with PAD independence ratio, effectiveness ratio, efficiency ratio and growth ratio. The result of the study shows that the independence ratio of PAD in Surakarta City 2020-2022 shows a consultative relationship pattern, namely that the level of regional dependence on assistance from the central government is close to being able to carry out autonomous affairs. The effectiveness ratio of Surakarta City’s PAD in 2020-2022 has been effective, namely average of 120% and it is already above 100%, the regional financial efficiency ratio of Surakarta City in 2020-2022has been efficient, namely an average of 95% or below 100% and the growth ratio Surakarta City in 2020-2022 has a positive value because it tends to increase, this occurs due to the maximum amount of revenue received by the Surakarta City Government. Keywords: Effectiveness ratio, efficiensy ratio and growth ratio, PAD independence ratio, and regional financial perfomance.